An LMI Approach to Hâ Performance Analysis of Continuous-Time Systems with Two Additive TimeVarying Delays - Ridwan, Wrastawa; Trilaksono, Bambang Riyanto (Journal of Engineering and Technological Sciences, 2011)
ThisÂ  paperÂ  investigatesÂ  theÂ  problemÂ  ofÂ  Hâ performanceÂ  analysisÂ  for continousâtime systems with two additive time -varying delays in the state.Â  Our objective is focused onÂ  stabilityÂ  analysis ofÂ  aÂ  continuousÂ  system with two timevaryingÂ  delaysÂ  withÂ  anÂ  Hâ disturbanceÂ  attenuationÂ  levelÂ  Î³.Â  ByÂ  exploiting Â Lyapunov-Krasovski functional and introducing free weighting matrix variables, LMI stability condition have been derived.